2022
DOI: 10.1109/access.2022.3140434
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Problem-Based Serious Games on Learning Motivation

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(24 reference statements)
0
7
0
1
Order By: Relevance
“…Therefore, the consumption of this educational video game can bring several educational and training benefits in various aspects, making it a game full of potential positive impacts. Educational benefits enhance the intrinsic motivation of the player to continue playing [31,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the consumption of this educational video game can bring several educational and training benefits in various aspects, making it a game full of potential positive impacts. Educational benefits enhance the intrinsic motivation of the player to continue playing [31,63].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies such as the one conducted by Nau and Liu [24] have also found that incorporating narrative elements into designs has been shown to be successful in terms of learning and encourages greater motivation. Likewise, Moradi and Noor [31] found that video game investment boosted players' intrinsic motivation to learn.…”
Section: Video Games and Educationmentioning
confidence: 95%
“…Several authors have contributed to enumerate the benefits of including SGs in teaching and learning processes. Giessen (2015) and Moradi and Noor (2022) highlight the motivating effect of SGs through the use of interactive and dynamic environments. Therefore, the goals and challenges that need to be overcome in the games keep students motivated and constitute a facilitating element to motivate students to discipline.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Serious games are playful and interactive tools often used in education with pedagogical goals, which are designed to teach skills, notions, and strategies [ 30 , 31 ]. Serious games offer active involvement, immediate feedback, experiential learning, collaborative learning, and learning personalization, which enhance positive learning effects [ 32 ]. The scenarios designed for serious games have a positive relationship with student engagement and academic performance [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage is immediate feedback, as they provide a timely and accurate response on the player’s actions, allowing learning based on error and its correction. Other advantages include experiential learning related to scientific literacy [ 58 ], as they allow for real-world situations to be experienced and simulated, providing a direct and engaging educational experience; collaborative learning, as they can be used to foster cooperative learning, stimulating participation and information sharing even in educational settings between teachers and students [ 59 , 60 ]; and learning personalization [ 61 ], as they can be designed to adapt to each player’s cognitive needs and abilities, sparking and maintaining player interest and motivation and enhancing positive learning effects [ 32 ]. In addition, there is a positive relationship between the scenarios designed for serious games and the expected outcomes of the learning experience [ 62 ] considering, as part of this process, student engagement and academic performance [ 33 ].…”
Section: Introductionmentioning
confidence: 99%